The role of non-governmental organizations in the formation of environmental policy and legal regulation of the People’s Republic of China - Geng, Ningjie (Frontiers in Environmental Science, 2025)
IntroductionCurrently, the issue of greening of law is becoming increasingly important in the context of preserving the environment, biodiversity and ensuring sustainable development. Within the frames of growing commitment to achieving environmental goals, this issue is of particular relevance for China. The response of civil legislation to the protection of the environment and resources is not only tied to the national conditions of the country and corresponds to its environmental aspirations, but also conditioned by the need to protect the health and wellbeing of the population. In this regard, the role of civil society and associations of citizens and non-governmental organizations is becoming a new lever for the formation of environmental policy and legislative regulation. This paper intends to assess the current status and role of NGOs in the legislative initiatives of the PRC on the greening of regulatory mechanisms in general and in the field of environmental policy formation.MethodsThe methodological basis is presented by the methods of political and legal and content analysis.Results and DiscussionThe results of the study indicate the limited role of modern NGOs in matters of legal initiative in general and in matters of greening of legislation in particular. At present, there is no clear evidence that NGOs are a direct influence on the law making. At the same time, one can note the increasing role of NGOs in the formation of environmental policy. The latter trend is noted against the background of a general increase in public involvement in environmental initiatives, as well as the expansion of civil rights in the field of ecology.